Beberapa Metodologi Pendidikan Melayu-Islam: Analisis Terhadap Manuskrip MSS 2906(A) Bab Al-Adab: Some Malay-Islamic Educational Methodology: An Analysis of Manuscript MSS2906(A) Bab Al-Adab - Mamat, Mohd Anuar (‘Abqari Journal, 2020)
The presence of Islam in the Malay Archipelago brings many changes, especially in the intellectual improvement of Malay society through educational institutions such as Quranic school and pondok. The educational institutions have successfully played an excellent role and have produced many scholars in various fields. Hence, this article aims to identify and analyse some Malay-Islamic educational methodology as understood by the Malays based on the manuscript of Bab al-Adab MSS 2906(A), held by the National Library of Malaysia. This article discussed on codicological analysis of the MSS 2906 concerning its origins, authorship and content. This article found that there are six educational methodologies mentioned by Bab al-Adab such as educational aim, learning preparation, knowledge integration, commitment in learning and apply various methods in acquiring knowledge. All these are aimed at exposing the roles and contributions of the Malay scholars in shaping the educational thought and methodology in the region as exemplified by various traditional educational institutions such as pondok, pesantren, dayah and meunasah.